Optimalisasi Kinerja Amil Melalui Budaya, Kreativitas, Sarana Prasarana dan Kepercayaan Pada Lembaga Amil Zakat (LAZ) di Kota Pekanbaru - Mardan, Jhonny Ardan (Jurnal Daya Saing, 2015)
Abstract: Issues raised in this study is the performance of the Institute Amil Zakat Zakat (LAZ) in Pekanbaru. The variables of this research is the influence of Organizational Culture, Creativity, Infrastructure and Communities Trust (the independent variable) and Amil performance (the dependent variable). The purpose of this study is to identify and analyze (1) the influence of the Influence of Organizational Culture Performance Amil, (2) the effect on the performance of Amil Creativity, (3) the effect on the performance of Amil Infrastructure, (4) the effect of Societies Trust Amil performance, (5 ) and the influence of Organizational Culture, Creativity, and Faith Community Infrastructure jointly on the performance of Amil. Object of this study is four Institute Amil Zakat (LAZ) are located in the city of Pekanbaru, LAZ Swadaya Ummah, LAZ Rumah Zakat, LAZIS Muhammadiyah and LAZNAS Chevron Rumbai, the number of Amil Zakat at 157 persons. The method used in this study is a quantitative method, and the entire sampling technique using proportional stratified random sampling technique. The results showed that the t value of 2.015 organizational culture variables is greater than t table (α / 2, n-2) = 2.000 means (2.015> 2.000 = Ho is rejected). For creativity variables (2.605> 2.000 = Ho rejected) means no influence on the performance of amyl creativity. T value of infrastructure variables (2.038> 2.000 = Ho rejected) no effect on the performance of amyl infrastructure. Last on the trust variables (2.178> 2.000 = Ho rejected) no effect on the performance of amyl confidence. Then the variable Organizational Culture, Creativity and Infrastructure and the trust jointly significant effect on the performance of the Institute Amil Amil Zakat (LAZ) in Pekanbaru which is equal to 0.507 or 50.7%. Keywords: Culture, Creativity, facilities and infrastructure, trust, performance Amil.